Original paperEvaluation of 101Rh as a brachytherapy source - Pakravan, Delaram; Ghorbani, Mahdi; Meigooni, Ali Soleimani (Journal of Contemporary Brachytherapy, 2015)
Purpose: Recently a number of hypothetical sources have been proposed and evaluated for use in brachytherapy. In the present study, a hypothetical 101 Rh source with mean photon energy of 121.5 keV and half-life of 3.3 years, has been evaluated as an alternative to the existing high-dose-rate (HDR) sources. Dosimetric characteristics of this source model have been determined following the recommendation of the Task Group 43 (TG-43) of the American Association of the Physicist in Medicine (AAPM), and the results are compared with the published data for 57 Co source and Flexisource 192 Ir sources with similar geometries. Material and method s: MCNPX Monte Carlo code was used for simulation of the 101 Rh hypothetical HDR source design. Geometric design of this hypothetical source was considered to be similar to that of Flexisource 192 Ir source. Task group No. 43 dosimetric parameters, including air kerma strength per mCi, dose rate constant, radial dose function, and two dimensional (2D) anisotropy functions were calculated for the 101 Rh source through simulations. Results : Air kerma strength per activity and dose rate constant for the hypothetical 101 Rh source were 1.09 ± 0.01 U/mCi and 1.18 ± 0.08 cGy/(h.U), respectively. At distances beyond 1.0 cm in phantom, radial dose function for the hypothetical 101 Rh source is higher than that of 192 Ir. It has also similar 2D anisotropy functions to the Flexisource 192 Ir source. Conclusions : 101 Rh is proposed as an alternative to the existing HDR sources for use in brachytherapy. This source provides medium energy photons, relatively long half-life, higher dose rate constant and radial dose function, and similar 2D anisotropy function to the Flexisource 192 Ir HDR source design. The longer half-life of the source reduces the frequency of the source exchange for the clinical environment.